Necessity of Changes in the System of Hospitality Industry and Tourism Training in Terms of Import Substitution - Zaitseva, Natalia A.; Goncharova, Irina V.; Androsenko, Marina E. (International Journal of Economics and Financial Issues, 2016)
The purpose of the authors in this study was to prove the relevance of research identifying the necessity of changes in the system of training for hospitality industry and tourism in terms of import substitution. The aim of this research was to assess the significance of tourism in the framework of import substitution, to justify the need for changes in the system of training for hospitality and tourism industry in recent situation. It is also essential to give practical recommendations on training and education development. The authors implemented expert assessment method and statistics analyses, tourists' questionnaires evaluating their travel preferences and personal materials and findings to enable construction of complex model of training and education development for hospitality industry. All above mentioned techniques allow authors to introduce their own findings concerning this issue in terms of import substitution. Through the study the authors scrutinize and generalize the problems concerning training and education for hospitality industry and give offers and solutions to improve activities most vital and perspective for the industry. The authors emphasize that it is essential not only to follow our national concept of import substitution but also to take into consideration the employers' requirements for staff working in hospitality. Furthermore, it is of vital importance to influence hospitality management to take part in educational programs development, while educators and scientists should introduce new technologies of customer service to the business organizations. As a result of implementing authors' recommendations given in the following article it will be likely to generate competitive tourism products and modernized educational programs which will meet customers' demands. The article findings are of practical importance for training and development in hospitality industry organization. It also has practical significance for all types of training organizations in hospitality industry and researchers of international training for the industry in the terms of import substitution. Keywords: Tourism. Import substitution. Personnel Training, Development. JEL Classifications: H25, H54, O14, Z31